POGIL Berpengaruh terhadap Kemampuan Berpikir Kritis Matematis? - Erlin Prihatami (AlphaMath : Journal of Mathematics Education, 2019)
Critical thinking is one of the skills students must have in mathematics learning so that students can make the right decisions when solving mathematical problems. This study aims to analyze the effects of the POGIL on students’ mathematical critical thinking skills. This research is an quasy experimental study, with a post test only control design research design. The population in this study were all students of grade VIII SMP N 2 Kemangkon in the academic year of 2018/2019. The sampling was done by cluster random sampling techniques and it obtained two sample classes namely class VIII C as an experimental class using learning with the POGIL model and class VIII B as control class using conventional learning models. The instrument used in this study was post-test mathematical critical thinking skill. Based on the result of hypothesis testing using independent sample t-test with a 95% confidence level, it shows that POGIL has an effect on students’ mathematical critical thinking skills.